Effects of deformation process on residual stress and grain size of magnesium alloy ZK60 / Syufiqa Nurfatin Rasid - Syufiqa Nurfatin, Rasid (2018)
This research investigates the residual stresses and grain sizes of Parallel Tubular Chanel Angular Pressing process (PTCAP) sample of 1,2 and 3 passes. PTCAP process is one of the new severe plastic deformation process (SPD) that is suitable for deforming cylindrical tubes to extremely large strains. Each sample will be under the same procedures. X-ray diffraction (XRD) measurement technique is adopted in this research as it is one of the most commonly used residual stress measurement technique. The sin²Ψ method is used to analyze the result accordingly. Meanwhile, Electro Discharge Machining (EDM) is used to cut the samples to fit inside the XRD machine. One peak angle of 2theta at the range 55° to 59° is evaluated accordingly. The same peak angle is also used to determine the grain size by applying Scherrer Equation and SEM analysis together with EDX. The results showed that the residual stresses for each sample varies randomly. The highest residual stress is 1659.2KN which occurred on sample of 2nd pass. Meanwhile for the grain size, it keeps increasing until the sample of 3rd pass. In this experiment, the grain size does not show any correlation with residual stress of the sample as the grain size increases while residual stress varies randomly.